A Pilot Study on Diagnostic Radiology Residency Case Volumes From a Canadian Perspective: A Marker of Resident Knowledge. Issue 4 (November 2020) - Kwan, Benjamin Y. M.; Mussari, Benedetto; Moore, Pam; Meilleur, Lynne; Islam, Omar; Menard, Alexandre; Soboleski, Don; Cofie, Nicholas
Purpose: New guidelines from the Accreditation Council for Graduate Medical Education (ACGME) have proposed minimum case volumes to be obtained during residency. While radiology residency programs in Canada are accredited by the Royal College of Physicians and Surgeons of Canada, there are currently no minimum case volumes standards for radiology residency training in Canada. New changes in residency training throughout Canada are coming in the form of competency-based medical education. Using data from a pilot study, this article examines radiology resident case volumes among recently graduated cohorts of residents and determines whether there is a correlation between case volumes and measures of resident success. Materials and Methods: Resident case volumes for 3 cohorts of graduated residents (2016-2018) were extracted from the institutional database. Achievement of minimum case volumes based on the ACGME guidelines was performed for each resident. Pearson correlation analysis (n = 9) was performed to examine the relationships between resident case volumes and markers of resident success including residents' relative knowledge ranking and their American College of Radiology (ACR) in-training exam scores. Results: A statistically significant, positive correlation was observed between residents' case volume and their relative knowledge ranking ( r = 0.682, P < .05). Residents' relative knowledge ranking was also statistically significant and positively correlated with their ACR in-training percentile score ( r = 0.715, P < .05). Conclusions: This study suggests that residents who interpret more cases are more likely to demonstrate higher knowledge, thereby highlighting the utility of case volumes as a prognostic marker of resident success. As well, the results underscore the potential use of ACGME minimum case volumes as a prognostic marker. These findings can inform future curriculum planning and development in radiology residency training programs.